A Novel and Generalized Three-Phase Power Flow Algorithm for Islanded Microgrids Using a Newton Trust Region Method - Abdelaziz, Morad Mohamed Abdelmageed; Farag, H. E.; El-Saadany, Ehab F.; Mohamed, Yasser Abdel-Rady I. (IEEE transactions on power systems, 2013)
A new formulation is required to provide a proper power flow analysis in islanded microgrids taking into consideration their special philosophy of operation. In this paper, a novel and generic three-phase power flow algorithm is formulated for islanded microgrids. The algorithm is novel since it adapts the real characteristics of the islanded microgrid operation; i.e., 1) some of the distributed generation (DG) units are controlled using the droop control methods and their generated active and reactive power are dependent on the power flow variables; 2) the steady-state system frequency is considered as one of the power flow variables. The proposed algorithm is generic, where the features of distribution systems, i.e., three-phase feeder models, unbalanced loads and load models have been taken in consideration. Further, all possible operation modes of DG units (droop, PV, or PQ) have been considered. The problem has been formulated as a set of nonlinear equations. A globally convergent Newton-trust region method has been proposed to solve this set of nonlinear equations. The proposed algorithm is a helpful tool to perform accurate steady state studies of the islanded microgrid. Different case studies have been carried out to test the effectiveness and the robustness of the proposed algorithm.